Effect of ammonia-oxidizing bacterial strain that survives drought stress on corn compensatory growth upon post-drought rewatering - Wang, Xiao-Ling; Ma, Ke; Qi, Lin; Liu, Yu-Hua; Shi, Jiang; Li, Xue-Lin; Zhang, Li-Xia; Liu, Wei; Song, Peng (Frontiers in Plant Science, 2022)
A pot experiment was performed under rain-shelter conditions to explore the effects of drought stress and post-drought rewatering on the abundance of an ammonia-oxidising bacteria (AOB) strain in corn (Zea mays L.) rhizosphere soils and the relationship between the AOB strain and corn (Zea mays L.) compensatory growth after drought stress rewatering. Corn seedlings were used as test materials, and one AOB strain was isolated and screened from soil. The experimental design included six treatments: ① wet (WT), ② wet with AOB strain inoculation during wetness (WI), ③ wet with AOB strain inoculation during rewatering (WR), ④ post-drought rewatering (DT), ⑤ post-drought rewatering with AOB strain inoculation during wetness (DI), and ⑥ post-drought rewatering with AOB strain inoculation during rewatering (DR). Wetness and drought stress were obtained by keeping the soil water content at 75%–80% and 50%–55% of the field capacities, respectively. The results showed that the isolated and screened AOB strain (S2_8_1) had 100% similarity to Ensifer sesbaniae. The inoculation of S2_8_1 during the wet period in the DI treatment caused it to colonize the rhizosphere soil. Drought stress decreased its abundance, but rewatering resulted in a great increase. The S2_8_1 in the DI treatment increased the total biomass, water use efficiencies, net photosynthetic rates, rhizosphere soil nitrification rates, leaf cytokinin concentrations, xylem sap cytokinin concentrations, copy number of S2_8_1 in rhizosphere soils and organic carbon contents in rhizosphere soils by 23%, 104%, 35%, 30%, 18%, 29%, 104%, and 23% on day 10 after rewatering compared with WT treatment. In the DI treatment, the increase in rhizosphere soil nitrification rates caused by S2_8_1 during wetness was closely related to the cytokinin delivery from roots to leaves and increased leaf cytokinin concentrations. The increase in leaf cytokinin concentrations improved rewatering corn growth, which caused compensatory growth and increased water use. Compensatory and over-compensatory growths occurred in DT and DR treatments, respectively. Therefore, the coexistence of the strain of AOB with corn in rhizosphere soil increased the corn compensatory growth by regulating soil nitrification and root-induced leaf cytokinin.